Extraperitoneal packing in unstable blunt pelvic trauma: A single-center study. Issue 5 (May 2020) - Frassini, Simone; Gupta, Shailvi; Granieri, Stefano; Cimbanassi, Stefania; Sammartano, Fabrizio; Scalea, Thomas M.; Chiara, Osvaldo
Abstract : BACKGROUND: Hemodynamically unstable pelvic fractures often require a multi-modal approach including both operative and endovascular management. While an important adjunct in hemorrhage control, time to angioembolization even at the most advanced trauma centers may take hours. Extraperitoneal packing (EPP) is a fast and effective procedure that can immediately address pelvic hemorrhage from the retroperitoneal space in severe pelvic injuries. The aim of this study was to evaluate the efficacy of early EPP, looking at 24 hours and overall mortality, and the hemodynamic impact of EPP in unstable blunt pelvic trauma. METHODS: All trauma patients admitted to an urban Level I trauma center were evaluated from 2002 to 2018 in a retrospective single-center comparative study. Inclusion criteria were patients 14 years or older who sustained blunt trauma with pelvic fractures and hemodynamic instability. Exclusion criteria were a concomitant head injury (Abbreviated Injury Scale >3) and patients who underwent resuscitative thoracotomy. The patient population was divided into two groups: an EPP group and a no-EPP group. Propensity score matching was used to adjust for differences in baseline characteristics in the two groups: a one-to-one matched analysis using nearest-neighbor matching was performed based on the estimated propensity score of each patient. RESULTS: Two hundred forty-four patients presented hemodynamically unstable, with a pelvic fracture (180 no-EPP, 64 EPP). With propensity score matching, 37 patients in each group were analyzed. Survival within the first 24 hours was significantly improved in the EPP group (81.1% vs. 59.5%, p = 0.042) and we registered similar results in overall survival rate (78.4% EPP group vs. 56.8% no-EPP group, p = 0.047). Those patients who underwent early EPP (n = 64) were associated with a significant improvement in hemodynamic stability, with a pre-EPP mean arterial pressure of 49.9 mm Hg and post-EPP mean arterial pressure of 70.1 mm Hg ( p < 0.01). CONCLUSION: Extraperitoneal pelvic packing is an effective procedure that can be performed immediately, even within the trauma bay, to improve hemodynamic stability and overall survival in patients who sustain severe blunt pelvic trauma. The early use of EPP can be lifesaving. LEVEL OF EVIDENCE: Therapeutic, Level III.